Extension as a living curriculum: a creditation experience of university extension in Caiçara communities of Guaraqueçaba-PR - Morais Barcelos, Jackson; Midori Kashiwagi da Rocha , Helena (Guará Journal, 2025)
This article presents a university extension experience developed on the coast of Paraná, in caiçara communities of Guaraqueçaba, as an integrative practice of teaching, research, and social action. The objective is to analyze the curricular integration of extension through the use of generative themes in teacher training, valuing territorial knowledge and rural education. The methodology adopted was qualitative, based on the systematization of experiences and participant observation, guided by authors such as Freire (1987), Arroyo (2012), and Demo (2000). The results indicate the effectiveness of extension as a tool for community (re)existence, humanizing education, and social transformation. Extension, in this context, not only complements the formal curriculum but also resignifies it, generating lasting impacts for both students and the communities involved.